2018
DOI: 10.1115/1.4040455
|View full text |Cite
|
Sign up to set email alerts
|

On Establishing Buckling Knockdowns for Imperfection-Sensitive Shell Structures

Abstract: This paper investigates issues that have arisen in recent efforts to revise long-standing knockdown factors for elastic shell buckling, which are widely regarded as being overly conservative for well-constructed shells. In particular, this paper focuses on cylindrical shells under axial compression with emphasis on the role of local geometric dimple imperfections and the use of lateral force probes as surrogate imperfections. Local and global buckling loads are identified and related for the two kinds of imper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Computationally, the only transition which has been followed previously is the simplest unbuckled-singly dimpled pathway, where the dimple is centrally located on the cylinder 32,33 . Meanwhile, local probing of cylindrical shells has been suggested as an experimental technique which may allow the true dimpling transition state to be accessed 26,[34][35][36] . In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computationally, the only transition which has been followed previously is the simplest unbuckled-singly dimpled pathway, where the dimple is centrally located on the cylinder 32,33 . Meanwhile, local probing of cylindrical shells has been suggested as an experimental technique which may allow the true dimpling transition state to be accessed 26,[34][35][36] . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An explicit link has therefore been made between the ease of single dimple formation and the sensitivity of loaded cylinders to lateral loading 32 . As important for structural applications, it has been suggested that these theoretical minimum-energy barriers can be accessed experimentally via a local probing technique for cylindrical 26,[34][35][36] and spherical shells 37,38 .…”
mentioning
confidence: 99%
“…Furthermore, while the SP-8007 guideline converges to P / P cl ≈ 0.2 for large R / t , the present shock-sensitivity threshold of figure 10 b converges to P / P cl ≈ 0.35 for large L 2 / Rt . It is interesting to note that in a recent publication [53] on imperfect cylinders, the knockdown factor approaches a similar value of P / P cl ≈ 0.35 with increasing dimple imperfection amplitude (normalized by cylinder thickness). Furthermore, this trend persists for different R / t and L / R ratios (assuming the cylinder is not very short), providing further credence to the newly developed knockdown factor.…”
Section: Buckling Design Load Based On Shock Sensitivitymentioning
confidence: 85%
“…Here, we show that the induced compression strain has the same effect than an external compression load applied to a shell with the same curvature: The geometric stability criterion c ∼ t/W with 1/W the typical curvature of the transversely curved sheet is the equivalent of the classical buckling of perfect cylindrical shells where the linear stability analysis predicts c = 1/ 3(1 − ν 2 )t/R [42] with ν denoting the Poisson coefficient of the shell and 1/R its curvature. Notably, the above-mentioned formula infamously overestimates the buckling load of cylindrical shells [44] because those systems are extremely imperfection sensitive [45,46]. This affects the reliability of thin shell structures, even for precisely manufactured shells, such as soda cans [47] and space rockets [44].…”
Section: Discussionmentioning
confidence: 99%